A implantação do Sistema de Gestão do Assentamento Funcional Digital (SGAFD) nos Institutos Federais de Educação do RS E SC: considerações arquivísticas - Flores, Simone Reis (2021)
The research addresses the implementation of the Digital Functional Settlement Management System in the Federal Institutes of Education of Rio Grande do Sul (RS) and Santa Catarina (SC) in order to develop and make available a summarized and easily accessible technical support instrument. it concerns the implementation procedures, observing the difficulties and successes as a result of the actions taken during the process. The AFD System is presented, in which a survey of the actions that facilitated the implementation in the IFES where the System was implemented and that participated in the research is carried out. The research identifies the main obstacles to implementation that have already been observed and presents possible causes of problems in the implementation of the SGAFD in the IFES, through the gathering of information to elucidate the problems that may occur in the implementation of the Digital Functional Settlement Management System. The collection of information is based on the application of the data collection script, with the application of an open-ended questionnaire with those responsible and professionals involved to learn about the management processes and institutional policies that involve the implementation of the SGAFD and serve as basis to achieve the final objective of the research, which is to develop and make available a support instrument for Federal Institutions in the implementation of the AFD System, thus achieving the result proposed in the dissertation.